High Figure of Merit (FOM) of Bragg Modes in Au‐Coated Nanodisk Arrays for Plasmonic Sensing. Issue 38 (21st August 2017) - Couture, Maxime; Brulé, Thibault; Laing, Stacey; Cui, Wenli; Sarkar, Mitradeep; Charron, Benjamin; Faulds, Karen; Peng, Wei; Canva, Michael; Masson, Jean‐Francois
Abstract : Gold‐coated nanodisk arrays of nearly micron periodicity are reported that have high figure of merit (FOM) and sensitivity necessary for plasmonic refractometric sensing, with the added benefit of suitability for surface‐enhanced Raman scattering (SERS), large‐scale microfabrication using standard photolithographic techniques and a simple instrumental setup. Gold nanodisk arrays are covered with a gold layer to excite the Bragg modes (BM), which are the propagative surface plasmons localized by the diffraction from the disk array. This generates surface‐guided modes, localized as standing waves, leading to highly confined fields confirmed by a mapping of the SERS intensity and numerical simulations with 3D finite element method. The optimal gold‐coated nanodisk arrays are applied for refractometric sensing in transmission spectroscopy with better performance than nanohole arrays and they are integrated to a 96‐well plate reader for detection of IgY proteins in the nanometer range in PBS. The potential for sensing in biofluids is assessed with IgG detection in 1:1 diluted urine. The structure exhibits a high FOM of up to 46, exceeding the FOM of structures supporting surface plasmon polaritons and comparable to more complex nanostructures, demonstrating that subwavelength features are not necessary for high‐performance plasmonic sensing. Abstract : Gold‐coated nanodisk arrays with near micron size features exhibiting excellent performances (high sensitivity, high figure of merit (FOM), and sharp plasmon resonance) are demonstrated with plasmonic sensing of a protein in urine and with large enhancement factor in surface‐enhanced Raman scattering. It is therefore shown that subwavelength features are not necessary to achieve large FOM and high‐performance plasmonic sensing.